EFEKTIVITAS MODUL KALKULUS INTEGRAL BERBANTUAN GEOGEBRA - Yeni Listiana Yeni; Aklimawati Aklimawati; Wulandari Wulandari; Erna Isfayani (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This research activity was motivated by the low learning outcomes of students in the Integral Calculus course and the unavailability of the GeoGebra-assisted Integral Calculus module in the Mathematics Education study program, Malikussaleh University. The purpose of the study was to determine the effectiveness of the GeoGebra-assisted Integral Calculus module. The type of research is development research with the Plomp development model which includes three stages of preliminary research, prototyping phase, and assessment phase. The test subjects were students of the Mathematics Education Study Program, Malikussaleh University. The instruments of this research are observation sheets of learning activities, student response questionnaires, observer response questionnaires to modules and test instruments. Based on the results of the study, it is known that the GeoGebra-assisted Integral Calculus module meets the effective criteria because the results of the learning activity observation sheets are in the very good category, student and observer responses to the module are in very good criteria and student test results have increased.